A Case of Business Opportunity Identification and Entry Into Entrepreneurship: A Socio-Cognitive Approach - Varghese, Dipu (AMC Indian Journal of Entrepreneurship, 2019)
Entrepreneurship viewed from a macro-level perspective can be considered as an interaction between entrepreneur and the external environment. Theories related to socio cognitive approach state that an individual’s behavior is affected by interaction between internal factors and external factors. The external environment plays a role in shaping intentions of entrepreneurs to start and develop their enterprise along with internal factors. This paper discusses the tale of an intrinsically motivated entrepreneur utilizing his social group, precisely, his friendship circle to identify an entrepreneurial opportunity and using the same for enterprise building.